Molecular and Enzymatic Characterization of Three Phosphoinositide-Specific Phospholipase C Isoforms from Potato - Kopka, Joachim (American Society of Plant Physiologists, 1998)
Many cellular responses to stimulation of cell-surface receptors by extracellular signals are transmitted across the plasma membrane by hydrolysis of phosphatidylinositol-4,5-bisphosphate (PIP(2)), which is cleaved into diacylglycerol and inositol-1,4,5-tris-phosphate by phosphoinositide-specific phospholipase C (PI-PLC). We present structural, biochemical, and RNA expression data for three distinct PI-PLC isoforms, StPLC1, StPLC2, and StPLC3, which were cloned from a guard cell-enriched tissue preparation of potato (Solanum tuberosum) leaves. All three enzymes contain the catalytic X and Y domains, as well as C(2)-like domains also present in all PI-PLCs. Analysis of the reaction products obtained from PIP(2) hydrolysis unequivocally identified these enzymes as genuine PI-PLC isoforms. Recombinant StPLCs showed an optimal PIP(2)-hydrolyzing activity at 10 μm Ca(2+) and were inhibited by Al(3+) in equimolar amounts. In contrast to PI-PLC activity in plant plasma membranes, however, recombinant enzymes could not be activated by Mg(2+). All three stplc genes are expressed in various tissues of potato, including leaves, flowers, tubers, and roots, and are affected by drought stress in a gene-specific manner.